Estrategias de internacionalización de empresas indias hacia Latinoamérica - Regalado-Pezúa, Otto (2019)
The objective of this publication is to analyze the ways of entry for the Indian companies in their internationalization’s process towards the Latin American market. The literature review and the results of the interviews with expert academics conclude that this process is affect by variables as; the country that receives the foreign investment; to the offer, the kind of company, economic sector in which it operates, and to the demand; the market where the company seeks to develop its internationalization. Five cases have been analyzed; two service companies: Tata Consultancy Services Limited and Oberoi Hotels & Resorts and three tangible product companies: Hero MotoCorp, Bajaj Auto and Mahindra. The limitations found show that there is a large field of action for future research on strategies for the internationalization of Indian companies to Latin America.